Glycosylated copper sulfide nanocrystals for targeted photokilling of bacteria in the near‐infrared II window - Hou, Shuai (2020)
Photothermal and photodynamic therapies are established as alternative approaches to combating bacterial infections; however, the heat and reactive oxygen species generated by the photoagents act on both normal and bacterial cells. A targeting strategy is thus required to minimize side effects and enhance the antibacterial efficiency. Glycoconjugates specifically interacting with bacterial lectins have emerged as a new class of materials for targeting bacteria. In this paper, galactosylated plasmonic copper sulfide nanocrystals (Cu2−xS NCs) are used to target Pseudomonas aeruginosa via galactose–LecA interactions and kill the bacteria by simultaneous photothermal and photodynamic therapy. Galactosylated Cu2−xS NCs are obtained by functionalizing the nanocrystals with tri‐thiogalactoside glycoclusters. The excellent specificity of galactosylated nanoparticles toward LecA with a LecA‐deficient P. aeruginosa strain as the control is first demonstrated. Afterward, a laser in the near‐infrared II window is used to kill the bacteria, and the critical role of targeted binding in efficient killing of bacteria is highlighted. This approach can be readily generalized to the targeting of other pathogens which have highly specific carbohydrate‐binding lectins.